A systematic literature review of the relationship between cultural intelligence and academic adaptation of international students - He Xiaoying; Sadiah Baharom; Liao Sunjing (Social Sciences and Humanities Open, 2023)
Achieving successful academic adaptation (AA) is crucial for assuring academic success and quality education for international students. Cultural intelligence (CQ) is found to be associated with the academic adaptation of international students. However, there was no systematic review of the relationship between cultural intelligence and academic adaptation. Therefore, this review attempted to present a clear picture of the relationship between cultural intelligence and academic adaptation in the setting of international students. After data analysis, it found that CQ and AA were linked through correlation and prediction and the relevant findings were contradictory. The contradictory statements can be attributed to factors related to research methods. This systematic review provides a new direction and constructive guidance for future investigation into a more complex theoretical model of the relationship between cultural intelligence and academic adaptation with better research design and more valid statistical analysis techniques.